2009
DOI: 10.1007/s10461-009-9576-4
|View full text |Cite
|
Sign up to set email alerts
|

Social Norms, Social Networks, and HIV Risk Behavior Among Injection Drug Users

Abstract: Social network structure and norms are linked to HIV risk behavior. However little is known about the gradient of norm of HIV risk that exists among social networks. We examined the association between injection risk network structure and HIV risk norms among 818 injection drug users (IDUs). IDUs were categorized into four distinct groups based on their risk behaviors with their drug networks: no network members with whom they shared cookers or needles, only cooker-sharing member, one needle-sharing member, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 32 publications
7
88
1
1
Order By: Relevance
“…For the items measuring knowledge of HIV transmission, correct answers were scored as '1' and incorrect answers were scored as '0'. The total score ranging from 0 to 14 was subcategorised into two categories (0-7 or [8][9][10][11][12][13][14]. Knowledge about the role of condoms in protection against STIs/AIDS was evaluated using a three-level variable (yes, no or never heard of condoms).…”
Section: Sti-related Knowledgementioning
confidence: 99%
“…For the items measuring knowledge of HIV transmission, correct answers were scored as '1' and incorrect answers were scored as '0'. The total score ranging from 0 to 14 was subcategorised into two categories (0-7 or [8][9][10][11][12][13][14]. Knowledge about the role of condoms in protection against STIs/AIDS was evaluated using a three-level variable (yes, no or never heard of condoms).…”
Section: Sti-related Knowledgementioning
confidence: 99%
“…Functional character-istics refer to the roles that network members play, such as sex partners or drug partners, as well as providing tangible (e.g., money, housing) or intangible (i.e., emotional) support. Social network members have been shown to infl uence health behaviors such as HIV risk practices (Latkin et al, 2010), tobacco and alcohol use among youth (Wenzel et al, 2010), and entry into treatment for substance use disorders (Davey et al, 2007).…”
Section: H Eavy Episodic Drinking (Hed) Frequency In the Unitedmentioning
confidence: 99%
“…A growing body of empirical research among various at-risk and minority youth populations suggests that fostering social interactions and perceived peer norms encouraging the practice of safer sexual behaviors may yield reductions in individual-level sexual risk behaviors (Albarracin, Kumkale, & Johnson, 2004;Dolcini et al, 2005). Studies among injection drug users (Davey-Rothwell, Latkin, & Tobin, 2010;Latkin et al, 2003;Latkin et al, 2009), young men who have sex with men (Peterson et al, 2009;Tobin & Latkin, 2008), and African-American youth (Brady et al, 2009a;Dolcini et al, 2010;Harper et al, 2004) have found that individuals who perceive their network members to support condom use were more likely to use condoms consistently. Dolcini and colleagues (2010) found that among African-American youth, a peer-based HIV/STI intervention focused on establishing positive peer norms around safer sexual behaviors successfully reduced multiple sexual partnerships and increased condom use and HIV testing (Dolcini et al, 2010).…”
mentioning
confidence: 99%